2022
DOI: 10.1002/cssc.202202161
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Aqueous Processing of Ni‐Rich Layered Oxide Cathode Materials by Addition of Lithium Sulfate

Abstract: Aqueous processing of Ni‐rich layered oxide cathode materials is a promising approach to simultaneously decrease electrode manufacturing costs, while bringing environmental benefits by substituting the state‐of‐the‐art (often toxic and costly) organic processing solvents. However, an aqueous environment remains challenging due to the high reactivity of Ni‐rich layered oxides towards moisture, leading to lithium leaching and Al current collector corrosion because of the resulting high pH value of the aqueous el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“… 29 In addition, the larger number of sulfonate groups present in the 3SO 3 – Carr binder may contribute to the protection of the NMC811 particles against water, achieving a more stable cycling than the 1SO 3 – Carr and 2SO 3 – Carr . This effect could be similar to the one observed by Heidbüchel et al 30 that have recently reported the positive impact of the addition of Li 2 SO 4 during the aqueous processing of NMC811 cathodes since a protective coating around the active material was observed by XPS measurements.…”
Section: Resultssupporting
confidence: 88%
“… 29 In addition, the larger number of sulfonate groups present in the 3SO 3 – Carr binder may contribute to the protection of the NMC811 particles against water, achieving a more stable cycling than the 1SO 3 – Carr and 2SO 3 – Carr . This effect could be similar to the one observed by Heidbüchel et al 30 that have recently reported the positive impact of the addition of Li 2 SO 4 during the aqueous processing of NMC811 cathodes since a protective coating around the active material was observed by XPS measurements.…”
Section: Resultssupporting
confidence: 88%
“…It is likely that phosphate surface species were also present in that case. Several other groups achieved higher initial DCs of up to 190 mAh/g CAM [18,27,44,45] . However, a lower ratio of anode:cathode capacity (N/P) was used within these studies, i. e., between 1.2 : 1 and 1.15 : 1.…”
Section: Resultsmentioning
confidence: 97%
“…Several other groups achieved higher initial DCs of up to 190 mAh/g CAM . [18,27,44,45] However, a lower ratio of anode: cathode capacity (N/P) was used within these studies, i. e., between 1.2 : 1 and 1.15 : 1. The N/P ratio of the cells in this study was 1.35 : 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations